Effect of Low Proportion Palm Biodiesel Blend on Performance, Combustion and Emission Characteristics of a Diesel Engine - Mohd Hafizil, Mat Yasin; Perowansa, Paruka; R., Mamat; Ahmad Fitri, Yusop; G., Najafi; Azri, Alias (Elsevier Ltd, 2015)
Short-term engine performance tests were carried out on diesel engine fuelled with diesel and B5 (5% palm methyl ester + 95% diesel) blended fuel. Blended fuels was conducted in a Mitsubishi 4D68 4 in-line multi cylinders compression ignition (CI) engine with various engine speeds to determine the torque and power of engine. Brake specific fuel consumption data also has been collected during the experimental tests. NOx, HC, CO2, CO, and O2 emissions also have been monitored has been collected. All parameters vary with engine speed. Results showed that at all engine speeds, torque and power outputs for B5 fuel were quite similar to neat petroleum diesel fuel. NO emission reduced significantly for both fuels but the rest emission contents were decreased with engine speed.